Microhaematuria - M. I. Kogan (Вестник урологии, 2025)
The May 2025 updates to the American Urological Association (AUA) and the Society for Urodynamics, Female Pelvic Medicine and Urogenital Reconstruction (SUFU) Microhaematuria (MH) Guideline 2020 have been published. The updates are based on the latest publications of the last five years and mainly address diagnostic programmes for bladder, upper urinary tract and renal parenchyma cancers. The importance of urinary markers, endoscopy, ultrasound and MRI to improve the diagnostic capabilities of tumour diseases is evaluated.